2017
DOI: 10.1117/1.jrs.11.016003
|View full text |Cite
|
Sign up to set email alerts
|

Mapping asphalt pavement aging and condition using multiple endmember spectral mixture analysis in Beijing, China

Abstract: Abstract. Asphalt road reflectance spectra change as pavement ages. This provides the possibility for remote sensing to be used to monitor a change in asphalt pavement conditions. However, the relatively narrow geometry of roads and the relatively coarse spatial resolution of remotely sensed imagery result in mixtures between pavement and adjacent landcovers (e.g., vegetation, buildings, and soil), increasing uncertainties in spectral analysis. To overcome this problem, multiple endmember spectral mixture anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…That is, the thermal radiation information will change based on the pavement conditions. Therefore, previous research has focused on obtaining the spectral data of target sections using multispectral or hyperspectral sensors and then evaluating pavement usage status by comparing and analyzing the spectral features of asphalt pavement at different ages [25]. For example, Mei et al analyzed field and laboratory data with the goal of differentiating asphalted surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…That is, the thermal radiation information will change based on the pavement conditions. Therefore, previous research has focused on obtaining the spectral data of target sections using multispectral or hyperspectral sensors and then evaluating pavement usage status by comparing and analyzing the spectral features of asphalt pavement at different ages [25]. For example, Mei et al analyzed field and laboratory data with the goal of differentiating asphalted surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the in situ measured spectra of asphalt road pavement showed that asphalt pavements in different aging conditions exhibit quite different spectral patterns over the range of 0.35 to 2.5 µm. The assessment of the analysis results showed that the method is capable of classifying road pavements with an overall accuracy of 81.71% and Kappa coefficient of 0.77, when the in situ data were used as a reference [25]. However, there are many disadvantages to identifying asphalt pavement distress using remotely sensed imagery, such as the high cost of data acquisition, the long data acquisition cycles, and the use of remote sensors that are not sufficiently flexible.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of pavement has a close relationship with the lifetime of road (Pan et al, 2017). In a general, because of the combined effect of aging and deterioration of road surface, some kinds of distresses would always appear on the pavement finally.…”
Section: Introductionmentioning
confidence: 99%